2016
DOI: 10.1186/s40064-016-1897-y
|View full text |Cite
|
Sign up to set email alerts
|

Double chamber right ventricle in Williams syndrome: a rare cardiac anomaly reported

Abstract: Cardiovascular abnormality is the most consistent finding and occur in almost 80 % of all Williams syndrome (WS). Although a number of cardiovascular defects are common to WS, the majority presents in some form of arterial stenosis whereas supravalvular aortic stenosis is the most common one. Here we describe a 12 year old boy with elfin facies, presenting with urinary incontinence and a systolic murmur in right upper parasternal region. Echocardiography showed presence of double chambered right ventricle (DCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Reference lists of journal studies were used to find further relevant journal articles. After obtaining journal permissions, photos of individuals with WBS were used to supplement study participants described below (Delgado et al, 2013; Honjo et al, 2015; Jiang & Liu, 2015; Lumaka et al, 2016; Mazumdar, Sarkar, Badveli, & Majumder, 2016; Morris, 1993, 2010; Patil, Madhusudhan, Shah, & Suresh, 2012; Sakhuja, Whyte, Kamath, Martin, & Chitayat, 2015; Smoot, Zhang, Klaiman, Schultz, & Pober, 2005; Tekendo-Ngongang et al, 2014; van Kogelenberg et al, 2010; Wu et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Reference lists of journal studies were used to find further relevant journal articles. After obtaining journal permissions, photos of individuals with WBS were used to supplement study participants described below (Delgado et al, 2013; Honjo et al, 2015; Jiang & Liu, 2015; Lumaka et al, 2016; Mazumdar, Sarkar, Badveli, & Majumder, 2016; Morris, 1993, 2010; Patil, Madhusudhan, Shah, & Suresh, 2012; Sakhuja, Whyte, Kamath, Martin, & Chitayat, 2015; Smoot, Zhang, Klaiman, Schultz, & Pober, 2005; Tekendo-Ngongang et al, 2014; van Kogelenberg et al, 2010; Wu et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Common pulmonary vein and left atrium anastomosis, and chordal reconstruction; repaired with the aid of hypothermic circulatory arrest Mazumdar et al 44 1 Double chambered right ventricle + coronary artery aneurysms (n = 1) 17 . Additionally, risks of anesthesia included craniofacial features causing difficult ventilation and tracheal intubation, variable reaction to neuromuscular blockade, and endocrine and metabolic disorders, which led to impaired hepatic drug metabolism and poor temperature regulation as have been indicated by Del Pasqua et al 6 Moreover, Yuan et al's 56 follow-up study revealed longterm sequelae of surgical resection, such as recurrence of SVAS, which might warrant reintervention.…”
Section: -Patch Techniquementioning
confidence: 99%
“…Hemizygosity of the ELN gene coding elastin has been demonstrated to be responsible for the vascular, and in part the cardiac, pathology in WBS; however, the mechanism is still unclear (Keating, ). Additionally, a double chamber right ventricle has been reported in relation to WBS (Mazumdar et al, ).…”
Section: Discussionmentioning
confidence: 99%